The investigation of the photophysical properties of α-chlorocurcumin and α-methylcurcumin - Saeed, Bahjat Ali (European Journal of Chemistry, 2015)
The electronic properties of α-chlorocurcumin and α-methylcurcumin was theoretically investigated at the B3LYP/6-311++G(d,p) level of theory. The thermodynamics quantities were estimated by calculating the frequencies of the molecules. Three main isomers were predicted after full geometry optimization of various suggested isomers within the tautomeric mixture of each molecule; the cis-enol, trans-enol and the trans-diketo isomers. Their stability was in the sequence: cis-enol > trans-diketo > trans-enol. The stabilization energy for the cis-enol with respect to trans-diketo and trans-enol in chlorocurcumin is 8.44 and 12.59 kcal/mol, respectively, while in methylcurcumin, it is 4.80 and 10.79 kcal/mol, respectively. The fluorescence spectra were recorded for the investigated compounds in several protic and aprotic solvent with different dielectric constants and H-bonding abilities. The emission maxima are within the range 487 to 571 nm in ethylene glycol, while they are within the range 475 to 557 nm in n-hexane. The fluorescence quantum yields of both compounds are low and lower than those of curcumin. The quantum yield of chlorocurcumin ranges from ΦFl = 0.008 in MeOH to ΦFl = 0.058 in toluene, while for methylcurcumin it ranges from ΦFl = 0.007 in DMF to ΦFl = 0.0524 in ethylene glycol. The fluorescence of both compounds quenched by water and their fluorescence life times are estimated from the slopes of the linear curves that obtained from Stern-Volmer relationship to be 1.44 and 1.40 psec for chlorocurcumin and methylcurcumin, respectively.